The Correlation Between Grammar Mastery and Writing Ability of The Eighth Grade Students - Muhammad Fahuzul; Badriyah Ulfah; Desi Surayatika (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Grammar is one of the aspects that are important in any skill of English including writing. The collaboration of grammar and writing is believed to affect the context and content to be attractive and easy to read by everyone. In this research, the researcher used the correlation method in quantitative. In collecting the data, the researcher used a grammar mastery exam with multiple choice questions and a writing ability exam with essay writing questions. As the result, this research represented that there was no significant correlation between students’ grammar mastery and writing ability. The results revealed that r-xy was less than r-table, or that 0,122 was less than 0,361. It was considered that the alternative hypothesis (H1) was rejected and the null hypothesis (Ho) was accepted. In the suggestion, students’ mastery of grammar was relatively low and requires more practice to achieve good results.